English language growth and the international student. - Rochecouste, Judith; Oliver, Rhonda (HERDSA Review of Higher Education v.1 p.63-81, 2014)
The provision of academic language and literacy support has undergone various reincarnations since the arrival of large cohorts of international students which placed additional responsibilities on Australian universities. Although initially a peripheral service accessed on a voluntary basis, the trend now is to reach more students by embedding such instruction within the disciplines. In this way students are assisted in addressing the specific literacy demands of their area of study. However, while language and academic support staff work closely to enhance students' assessment outcomes, the focus of instruction remains for the most part on the written product. In this article the authors report on an investigation of international students' learning strategies and specifically those instigated outside their formal learning activities. In particular, the authors present those affective variables that positively impact on the students' desire to improve their English language skills. Using methodology informed by Second Language Acquisition research, these learning strategies were classified as social, cognitive and metacognitive. Their use was then matched with GPAs, or normalised equivalents, to ascertain their effectiveness in relation to academic achievement. [Author abstract]